Penerapan Paradigma Etika Antroposentrime Moderat dan Eksistensialisme Martin Heidegger dalam Pembagunan IKN - Bima, Irenius (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This research focuses on the application of the ethics of Moderate Anthropocentrism and Martin Heidegger's Existentialism in the development of the new IKN in East Kalimantan. So far, development in Indonesia has paid little attention to environmental impacts and the existence of other humans. Development in Indonesia tends to be exploitative and development orientation is centered on human interests alone, without being based on sustainable development. A shallow understanding of the meaning of Anthropocentric and existentialist causes social inequality, uneven development and many environmental problems. Therefore, the application of Moderate Anthropocentrism ethics and Martin Hiedegger's deep Existentialism meaning in the development of the new IKN helps humans as the center of life to treat nature and others fairly and responsibly. The development of the capital city pays more attention to the balance between human interests and environmental sustainability. Thus, the development of IKN will be sustainable and the new IKN can become an effective and efficient economic center. The method used in the research is qualitative method through literature study. This research found that the application of Martin Hiedegger's Moderate Anthropocentrism and Existentialism ethics has great implications in building IKN, namely sustainable development goals (SDGs). This research contributes to the improvement of human resources (HR) and strict sanctions for violators of the IKN Law.